Reconstruction of Moral Philosophy as a Way of Salvation in the Middle of Contemporary Ethical Thought - Alfiansyah Anwar; Ibrahim, Musdalifa (IAIN Parepare, 2023)
The aims of this research are (1) to know the response of moral philosophy to contemporary ethical thinking (2) to know the position and response of moral philosophy to contemporary ethical thinking (3) to know the solutions to contemporary problems. The type of research used in this research is qualitative research. This study uses a library study approach because it collects data from books, journals, the internet, or other written literature as a basis for writing. The results of this study indicate that: (1) the response of moral philosophy to contemporary ethical thinking is that the study of morality and ethics has the same goal but has differences in terms of defining its goals. Ethics as part of philosophy bases its theory on relative logic while moral philosophy bases it on transcendent revelation (2) when ethics is used as a sub of philosophy, ethical philosophy will include moral philosophy. Morals are not ethics but they both have something in common, that is, they both discuss good and bad issues. The difference is that morals are closer to manners and are applicable in nature, while ethics tend to be more philosophical (3) Solutions to contemporary problems: first, it is necessary to uphold justice as an ethical solution. Second, the need to develop a caring and responsible character. Third, the need for socialization and teaching of moral philosophy from an early age.